Telomere shortening and cell senescence induced by perylene derivatives in A549 human lung cancer cells - Taka T. (2014)
Cancer cells evade replicative senescence by re-expressing telomerase, which maintains telomere length and hence chromosomal integrity. Telomerase inhibition would lead cancer cells to senesce and therefore prevent cancer cells from growing indefinitely. G-quadruplex ligands can attenuate telomerase activity by inducing G-quadruplex formation at the 3′-overhang of telomere and at the human telomerase reverse transcriptase (hTERT) promoter; the former prevents telomerase from accessing the telomere, and the latter acts as a transcriptional silencer. The present investigation found that perylene derivatives PM2 and PIPER induced G-quadruplex formation from both telomeric DNA and the hTERT promoter region in vitro. Further, TRAP assay showed that these compounds inhibited telomerase in a dose-dependent manner. When A549 human lung cancer cells were treated with these compounds, hTERT expression was down-regulated. Moreover, the crude protein extract from these treated cells exhibited less telomerase activity. In the long-term treatment of A549 lung cancer cells with sub-cytotoxic dose of these perylenes, telomere shortening, reduction of cell proliferation and tumorigenicity, and cell senescence were observed. The results of this study indicate that perylene derivatives warrant further consideration as effective agents for cancer therapy. © 2012 Elsevier Ltd. All rights reserved.